Associations Between Thyroid and Blood Pressure in Euthyroid Adults: A 9-Year Longitudinal Study - Abdi, Hengameh; Gharibzadeh, Safoora; Tasdighi, Erfan; Amouzegar, Atieh; Mehran, Ladan; Tohidi, Maryam; Azizi, Fereidoun (Hormone and Metabolic Research, 2018)
Longitudinal studies considering associations between thyroid function in the reference range (RR) with blood pressure (BP) are scarce and contradictory. We aimed to investigate the associations of serum thyrotropin (TSH) and free T4 (FT4) with different components of BP also incident prehyperetension (preHTN) and HTN during a 9-year follow-up. A sum of 2282 euthyroid individuals from an ongoing population-based cohort study were selected. A sex-stratified multivariate generalized estimating equation (GEE) method was employed. Moreover, a multivariate transitional model was used considering preceding BP status as a predictor of dichotomous outcomes of preHTN and HTN. Multivariate-adjusted GEE analysis revealed a decreasing trend for systolic BP (SBP), diastolic BP (DBP), mean arterial pressure (MAP) and pulse pressure (PP) throughout the study period in both men and women, either adjusted for serum TSH or FT4 levels. Serum FT4 within the RR was positively associated with all BP parameters in total population and in men, but serum TSH had a statistically significant mild increasing effect only on SBP, DBP and MAP of men. Multivariate transitional model found no association between serum TSH levels within the reference range (RR) and BP status; regarding serum FT4, a 1 ng/dl higher FT4 was associated with 40% increased risk of preHTN [OR (95% CI), 1.40 (1.02–1.90)], but not with HTN [OR (95% CI), 0.93 (0.80–1.09)]. It is concluded that serum FT4 within the RR is more strongly associated with BP parameters compared to TSH. This association is not consistent between men and women. Moreover, higher FT4 is associated with increased risk of preHTN.
Keywords: thyroid-stimulating hormone; thyroxine; blood pressure